(untitled) (Fiep Bulletin - online, 2013)
Aiming to encourage self-perceived baccalaureate the 3rd period of Physical Education, Faculty of Physical Education and Physiotherapy, Universidade Federal do Amazonas (FEFF-UFAM), the teaching of the discipline Process and Motor Learning proposed that they fulfilled concerning themselves, scoring from 0 to 10, three blocks of activities: locomotion, manipulation and combination. The subjects were 26 students, 17 male and 9 female, who answered individually at home and made the sum of points and the average of each of the 3 dimensions. Data were entered into an Excel spreadsheet and using the statistical program minitab being obtained medias overall and by sex. The results indicated that the overall averages were: 6.05 for locomotion, manipulation 7.56 and 6.82 combination. The averages were classified by sex for Locomotion: Male 6.65, with standard deviation 1.18, Female 4.92, standard deviation 1.09; Manipulation for: male 8.10 with standard deviation 1.05, female 6.58, and 0.98 standard deviation for Combination: Male 7.48 with standard deviation 1.07; Male 5.60 standard deviation 0.616. Comparing the averages with the Student t test, in all cases there are differences between the sexes. It is concluded that the abilities highlighted showed that females there is a need of improvement concerning the same media, on the other hand, the skills male need to add to what has already assimilated, suggesting that both must seek greater repertoire motor, even if it does not reach the stereotype dynamic driving, or mature stage of all items. Considering them as academics Physical Education, and that the ability of human movement is unlimited, their experience of movement should be further developed, as is the raw material of professional practice, which may facilitate or non-performance by the professional scope.